2017
DOI: 10.1093/ehjci/jex156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical dyssynchrony of the left atrium during sinus rhythm is associated with history of stroke in patients with atrial fibrillation

Abstract: Higher mechanical dyssynchrony of the LA during sinus rhythm is associated with a history of stroke/TIA in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…Other studies also subsequently demonstrated that increased LA size as characterised by LA volume, even in patients with no prior AF, was predictive of first ischaemic stroke, incremental to other established stroke risk factors 6 21. Evidence from population-based studies indicates that LA enlargement is associated with ischaemic stroke independently of diagnosed AF 22–24. The novelty of our study shows that geometric shape of the LA is more reflective of the blood flow profile within the LA, which mechanistically explains the increased risk of stroke.…”
Section: Discussionsupporting
confidence: 65%
“…Other studies also subsequently demonstrated that increased LA size as characterised by LA volume, even in patients with no prior AF, was predictive of first ischaemic stroke, incremental to other established stroke risk factors 6 21. Evidence from population-based studies indicates that LA enlargement is associated with ischaemic stroke independently of diagnosed AF 22–24. The novelty of our study shows that geometric shape of the LA is more reflective of the blood flow profile within the LA, which mechanistically explains the increased risk of stroke.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, in individuals with A‐IAB, low LA strain rate during atrial contraction (Sra) by speckle‐tracking echocardiography predicts incident AF and ischemic stroke 8 . LA volumes, strain, dyssynchrony, and fibrosis are also predictors of stroke, 9,10 incident AF, 11 and AF recurrence after catheter ablation 12‐14 . Understanding which features of LA structural remodeling are associated with A‐IAB would improve the diagnostic and prognostic value of 12‐lead ECG.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of inter‐atrial dyssynchrony has been recently highlighted. It was found to be a putative mechanism for cardioembolic stroke in the absence of atrial fibrillation . In this way, inter‐atrial dyssynchrony can be viewed as a feature of atrial cardiopathy, a syndrome linking LA dysfunction in the absence of atrial fibrillation to increased risk of thromboembolism …”
Section: Discussionmentioning
confidence: 99%